Manufacturing Celebrity : Latino Paparazzi and Women Reporters in Hollywood - Díaz, Vanessa, 1983- (Book collections on Project MUSE., 2020)
"MANUFACTURING CELEBRITY examines the gendered, racialized, and classed organization of labor in the production of celebrity media through an ethnographic exploration of the two groups who create the material that populates celebrity news magazines: the predominantly Latinx men who work as paparazzi, and the predominantly white women reporters who write for weekly entertainment magazines. Vanessa Diaz examines how the politics of visibility/invisibility affect those who create celebrity media, and interrogates how the social relations and subject positions of media producers shape the stories they tell, which in turn shapes how Americans relate to celebrities. For example, Diaz illustrates that while white female entertainment reporters often have access to the industry through racialized and classed visibility, they and their labor are often sexualized, manipulated, and used strategically by superiors and interview subjects. On the other hand, the Latinx men who work as paparazzi are often only able to gain entrance to the entertainment industry through paparazzi work, which doesn't require specialized training or a college degree; as a result, paparazzi work is not only precarious but raced, and paparazzi are often the subjects of public rage. Drawing on ethnographic research and her own personal experiences while working as a writer for People magazine, Diaz analyzes how weekly celebrity magazines construct celebrities that are "just like us," and interrogates the gendered, raced, and classed position of that "us." The book is divided into three sections: the first focuses on the paparazzi; the second on celebrity reporters; and the third on strategies celebrity weeklies use to create audience investment in celebrity culture. Chapters 2, 3, and 4 detail the job of the paparazzi, examine the economics of paparazzi work, and center the story of Chris Guerra, a paparazzo who died on the job, to explore the violence and precarity that paparazzi face. Chapters 5 and 6 examine the spaces where celebrity reporting takes place: the red carpet, but also nightclubs, public spaces, and one-on-one interviews. Chapters 7 and 8 analyze two tactics popular in celebrity weeklies: reports on celebrities bodies (the beach body, or the pregnant body), and the celebrity couple name-combining (i.e. Brangelina for Brad Pitt and Angelina Jolie). This book will be of interest to students and scholars of anthropology, popular culture, media studies, feminism and gender studies, Latinx studies, and critical ethnic studies"--